BIOELECTRICITY GENERATION AND TREATMENT OF PETROLEUM REFINERY EFFLUENT BY BACILLUS CEREUS AND CLOSTRIDIUM BUTYRICUM USING MICROBIAL FUEL CELL TECHNOLOGY (Nigerian Journal of Technology, 2017)
Microbial fuel cells (MFCs) being an emerging technology have been the research focus of increasing interest due to their sustainable capacity for wastewater treatment together with electricity generation. This study investigated the potential use of pure culture Bacillus cereus and Clostridium butyricum as inoculums in MFCs for simultaneous bioelectricity generation and treatment of petroleum refinery effluent. Double-chambered MFCs was used for the study and operated over four-batch cycles for 30 cumulative days but with different external resistances. The influent concentrations of chemical oxygen demand (COD) and total organic compound (TOC) in the petroleum refinery effluent was 970 mg/l (ppm) and 156 g/l, respectively. Experimental results indicated that the MFCs with the use of Bacillus cereus as biocatalyst achieved its maximum COD removal, TOC degradation and coulombic efficiencies of 70%, 88.7% and 19.21%, respectively; while with the use of Clostridium butyricum, it achieved the highest COD removal, TOC degradation and coulombic efficiencies of 54.2%, 68.7% and 17.84%, respectively. A maximum voltage of 450 mV and highest power density of 17066.67 mW/m2 with a maximum current density of 1.270 mA/m2 was obtained in regard to the external resistor of 1000 ? using Bacillus cereus as biocatalyst. Similarly, using Clostridium butyricum as biocatalyst the maximum voltage of 370 mV and highest power density of 8816.17mW/m2 with a maximum current density of 0.913 mA/m2 was achieved. The study demonstrated that both Bacillus cereus and Clostridium butyricum has strong potentials to be used as inoculums for simultaneous bioelectricity generation and treatment of petroleum refinery effluent in MFCs.http://dx.doi.org/10.4314/njt.v36i2.30